Elena Castroviejo, Louise McNally e Galit Sassoon (Eds.). The Semantics of Gradability, Vagueness, and Scale Structure. Experimental Perspectives - Cantante, Inês (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2021)
.